Using a value chain framework for food safety assessment of broiler and indigenous chicken meat systems of Nairobi - Carron, M.; Alarcón, Pablo; Häsler, Barbara; Fèvre, Eric M.; Karani, M.; Muinde, P.; Akoko, James M.; Onono, J.; Rushton, Jonathan (International Livestock Research Institute, 2015)
Purpose: Research on livestock food systems in developing countries remains limited, yet this context needs to be understood to investigate the epidemiology of zoonoses. The aim of this study was to use a value chain framework to characterize the broiler and indigenous chicken meat systems of Nairobi and their food safety risks. Methods: Using such a framework for food safety characterisation at system level is novel and has significant potential in developing countries. Data collection involved 18 focus group discussions and 236 interviews with various poultry meat value chain stakeholders in Nairobi. Analysis included chain mapping and identification of governance and food safety challenges. Results: The study identified 10 chain profiles, characterising the broiler and indigenous chicken systems, and production-retailing continuum. Food safety risks identified were related to lack of biosecurity, cold chain and access to water, poor cleaning and hygiene practices, consumption of sick animals, significant environmental contamination of by-products, and lack of inspection at farm slaughter. Large companies dominated the governance of the broiler system through the control of day-old chick production. Overall government control was relatively weak leading to minimal official regulatory enforcement. Large companies and brokers were identified as dominant groups in market information dissemination and price setting. No dominant group was identified for indigenous chicken profiles, farming being at household level for local consumption, with quasi non-existent regulations. Lack of industry association was system-wide, creating a barrier for access to capital. Other system barriers included lack of space and expertise, leading to poor infrastructure and limited ability to implement effective hygienic measures. Conclusions and relevance: Optimal food safety and disease control strategies should consider the structure of the poultry meat system and stakeholder interactions to ensure effective programmes. This study provides a new perspective for epidemiologists and public health officers to address food safety risks in full understanding of the food system context.